Cross‐Batch Contamination in a Continuous Horizontal Decanter Centrifuge during Virgin Olive Oil Production. Issue 2 (18th December 2022) - Guerrini, Lorenzo; Corti, Ferdinando; Masella, Piernicola; Calamai, Luca; Angeloni, Giulia; Spadi, Agnese; Zanoni, Bruno; Parenti, Alessandro
Abstract: Cross‐batch contamination in a decanter centrifuge during virgin olive oil production cannot be avoided using current technology. The extent of this contamination is investigated using industrial‐scale tests, by measuring the volatile profile and color on three consecutive oil batches, collected at the decanter outlet at different extraction times. The extent of contamination varied, pointing out qualitative consequences, as defective molecules are found. The latter are often active at low concentrations, and the measured cross‐batch contamination can lead both to the downgrading of large batches of virgin olive oils and to the adulteration of monovarietal and certified productions. An innovative method, based on the direct determination of the color ( L and a* coordinates) of oil at the outlet of the decanter is able to identify the same compositional change point indicated by gas chromatography, and could be successfully used to mitigate the effects of cross‐batch contamination. Practical applications : An in‐line colorimetric system can be implemented at the decanter outlet to detect the point of change between different olive batches. Otherwise, the virgin olive oil exiting from the decanter at the beginning of one batch can be collected separately in order to avoid the contamination due to the previous batch. Abstract : The extent of cross‐batch contamination in a decanter centrifuge is investigated during virgin olive oil production, measuring the volatile profile and color on three consecutive oil batches, sampled at the decanter outlet at different extraction times. CIELab coordinates identify the same compositional change point indicated by chromatography. Thus, an in‐line colorimetric system can be implemented to avoid such drawback.